Teaching English for Young Learners Using Vocabulary Cards - Sriwulandari, Novi; Yaqin, Muhammad Ainul; Dewi, Risma Kartika; Ihsan, Mas Darul; Trisnantasari, Ika; Ndaung, Ernita (Academia Publication, 2021)
Introducing English to children aged 0-12 years as a foreign language is very important considering that they are in the